Heating Method Effect on SnO Micro-Disks as NO2 Gas Sensor - Masteghin, Mateus G.; Godoi, Denis R. M.; Orlandi, Marcelo O. (Frontiers in Materials, 2019)
There is an increasing concern about NOx emission, and many studies have been carried out using metal oxide semiconductors (MOS) aiming its detection. Among the MOS, the SnO micro-disks present a high sensor response and a great selectivity toward NO2. Nevertheless, sensor signal, limit of detection (LOD), and recovery time are related to the experimental setup used to carry on the measurements. Thus, two different heating methods (self-heating and external heating) have been carried out to understand in what manner they change the sensor properties of the SnO micro-disks onto interdigitated electrodes. The external heating method presented higher sensor signal, best LOD, and lower recovery time, mainly due to the lack of a temperature gradient between the SnO disks and the chamber atmosphere. On the other hand, response time was shown to be the same regardless of the method. Briefly, the authors used thermodynamic equations to better understand the temperature effect on the gas-solid interactions occurring between SnO disks and NO2 species.